Stochastic Quantization of the Chern-Simons Theory - Cugliandolo, Leticia F. (1992)
We discuss Stochastic Quantization of d=3 dimensional non-Abelian Chern-Simons theory. We demonstrate that the introduction of an appropriate regulator in the Langevin equation yields a well-defined equilibrium limit, thus leading to the correct propagator. We also analyze the connection between d=3 Chern-Simons and d=4 Topological Yang-Mills theories showing the equivalence between the corresponding regularized partition functions. We study the construction of topological invariants and the introduction of a non-trivial kernel as an alternative regularization.